Multisensory mental representation in covid-19 patients and the possibility of long-lasting gustatory and olfactory dysfunction in the CNS - Barbara Tomasino; Gaia Pellitteri; Francesco Bax; Alessandro Marini; Andrea Surcinelli; Gian Luigi Gigli; Mariarosaria Valente (Scientific Reports, 2022)
Abstract Gustatory (GD) and olfactory (OD) dysfunctions are the most frequent neurological manifestations of COVID-19. We used mental imagery as an experimental psychological paradigm to access olfactory and gustatory brain representations in 80 Italian COVID-19 adult patients (68.75% reported both OD and GD). COVID-19 patients with OD + GD have a significantly and selectively decreased vividness of odor and taste imagery, indicating that COVID-19 has an effect on their chemosensory mental representations. OD + GD length and type influenced the status of mental chemosensory representations. OD + GD were become all COVID-19 negative at the time of testing. Data suggest that patients are not explicitly aware of long-term altered chemosensory processing. However, differences emerge when their chemosensory function is implicitly assessed using self-ratings. Among patients developing OD + GD, self-ratings of chemosensory function (taste, flavor) were significantly lower as compared to those who did not. At the level of mental representation, such differences can be further detected, in terms of a reduced ability to mentally activate an odor or taste mental image. Our study shows that COVID-19 infection not only frequently causes hyposmia and dysgeusia, but that may also alter the mental representations responsible for olfactory and gustatory perception.